Re-examination of the hypothesis of twin deficits in developing countries : A case study of Congo - Ngakosso, Antoine (DEMO, 2021)
This research paper mainly aims to re-examine the hypothesis of twin deficits in Congo using both a linear model and a threshold effect model with public debt as the threshold variable. It comes out that the two models converge and confirm the hypothesis of twin deficits in Congo. However, the only difference is that the threshold effect model determined the public debt threshold at 102.94% which changes the budget deficit path of the external deficit. This public debt threshold is much higher than the public debt sustainability threshold, which is around 40%. The difference between the two public debt thresholds has strong implications upon the economic policy. Thus, for public debt levels below 40%, the problem of rebalancing the external balance does not matter. Between 40% and 102.94%, a gradual fiscal consolidation is recommended to restore external balance. Above 102.94%, shock therapy should be considered first, then gradual fiscal consolidation should be considered when the debt falls below 102.94%.(original abstract)
Keywords: Public debt; Budget deficit; Debt; Developing countries